Root Growth and Distribution Pattern in Luceana Leuccephala, Gliricidia Sepium and Senna Siamea in the Humid Lowlands of Ghana (Journal of Science and Technology, 2016)
Horizontal and vertical distribution of roots of one year old Luceana elecucephala, Gliricidia sepium and Senna siamea plants on field plots were studied using the skeleton (dry excavation) method. Root systems of the three species generally consisted of a strong downward growing tap root with laterals originating from the main root axis. In Luceana and Senna, roots developed faster than shoots, and at the end of nine weeks after sowing, mean root length shoot height ratios were 1.41 and 1.46 respectively. Total root biomass ranked in the order Senna > Glircidia > Leucaena. The bulk (an average of about 81%) of the root biomass are found in the top 15cm depth of the profile. Horizontal root spread varied from 98.2cm in Leucaena to 104.7cm in Senna. Active noodles were observed on the roots of Leucaena and Glircidia but not Senna. This study concludes that the three species are likely to compete with agricultural crops for water and nutrients when grown together.